STRATEGI KOMUNIKASI KOMISI PENYIARAN INDONESIA DAERAH (KPID) DALAM MENDORONG PENYIARAN PERBATASAN (Studi Kasus KPID KEPRI Periode 2011-2014) - Intan Tri Kusumaningtias (Universitas Pakuan, 2018)
AbstractIndonesia is a country that consist of many island. There are 12 island which in border to the neighboring countries. Which include Riau island Province (Kepri). Kepri is a wide range of area despite of the small population. The Population density is only located in Batam city, Karimun and Bintan island. Regions border has complex issue, causing a foreign broadcast entering the Riau Island Province, hence lack of interest for investors to organize the broadcast in maritime province.Strategy is the source used to help a management to achieve a goal. The purpose of this process is to achieve the goal that has been pointed. Meanwhile, management theory known as (POAC) intended to know the planning, organizing, actuating, controlling and evaluating.Studies show to use descriptive feature. Method used is the method of case study, which perform to approach the qualitative, that aims the result of observation and interview with few resources from Head of Commision Broadcast Region of Indonesia (KPID) Riau Island Province, Head of Sub Section(Kasubag) KPID Kepri, Director PT Radio Azam Mitra Umat.The conclusion from the studies communication strategy between KPI, KPID, KPIDP and institute involved and also military is encourage to join forces to spread the information in the border region, to protect the sovereignty and conserve culture In Riau island province which is Melayu culture.Keyword: Communication strategy, Commision Broadcast Region of Indonesia, Region Border